2021
DOI: 10.1038/s41598-021-88789-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer development in patients with keloids

Abstract: Keloid is a skin disease characterized by exaggerated scar formation, excessive fibroblast proliferation, and excessive collagen deposition. Cancers commonly arise from a fibrotic microenvironment; e.g., hepatoma arises from liver cirrhosis, and oral cancers arise from submucosal fibrosis. As keloids are a prototypic fibroproliferative disease, this study investigated whether patients with keloids have an increased cancer risk. In a matched, population-based study, first 17,401 patients treated for keloids dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…It is difficult to achieve a complete cure for this disease. Moreover, recent studies have indicated that patients with keloids have a higher risk of developing various cancers than normal individuals ( Lu et al, 2021 ). In a matched, population-based regression analysis study (17,401 patients with keloid vs. 69,604 controls), Ying-Yi et al have shown that the overall cancer risk was 1.49-fold higher in the keloid group than controls ( Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to achieve a complete cure for this disease. Moreover, recent studies have indicated that patients with keloids have a higher risk of developing various cancers than normal individuals ( Lu et al, 2021 ). In a matched, population-based regression analysis study (17,401 patients with keloid vs. 69,604 controls), Ying-Yi et al have shown that the overall cancer risk was 1.49-fold higher in the keloid group than controls ( Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keloids grown in certain areas can also become symptomatic by limiting joint mobility and even causing deformity. Although keloids have been considered benign, growing evidence shows that the underlying pathogenesis and recurrent episodes entail regular skin examinations as the keloid-prone population faces a significantly higher risk of developing skin cancer, especially males [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although keloid is labeled as an abnormal but benign dermal growth where excessive scar tissue results from failed suppression of wound healing, it resembles malignant tumor cells in terms of its hyperproliferative nature and capability of invasion. There is also growing evidence showing that keloid-prone populations, especially males, face a significantly higher risk of developing skin malignancies [ 11 ]. This, along with the cosmetic burden and disabling potential of large keloids, entails more advanced, effective treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas hypermethylation can cause downregulation and inhibit transcription and synthesis of tumor suppressor proteins, hypomethylation can destabilize the DNA and be a precursor for oncogenesis. The significance of oncogenesis in the development of keloids is underscored by findings that aberrant methylation of tumor suppressor genes appears to be a factor in the development of keloids [ 15 ] and patients affected by keloids exhibit increased incidences of various skin cancers [ 16 ]. Figure 2 summarizes the role of DNA methylation in the formation of keloids.…”
Section: Reviewmentioning
confidence: 99%
“…Inhibition of migration and proliferation of keratinocytes adversely affect wound epithelialization and, ultimately, wound healing. ROS is associated with increased expression of the GLUT1 glucose transporter in the skin of patients affected by diabetes [ 26 ], psoriasis [ 27 ], and keloids [ 16 ], thereby providing a biochemical marker for oxidative stress and the potential for developing fibroproliferative lesions. Increased ROS in fibroblasts from keloid scar tissue exposed to hypoxia [ 28 ] also suggests that oxidative stress likely plays an important role in the development and maintenance of keloids.…”
Section: Reviewmentioning
confidence: 99%